2019
DOI: 10.3390/antiox8120629
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Glutathione Peroxidase Activity and Central Obesity in Patients with Type 2 Diabetes at High Risk of Cardio-Renal Disease

Abstract: Women with type 2 diabetes (T2DM) have an increased susceptibility of developing cardio-renal disease compared to men, the reasons and the mechanisms of this vulnerability are unclear. Since oxidative stress plays a key role in the development of cardio-renal disease, we investigated the relationship between sex, plasma antioxidants status (glutathione peroxidase (GPx-3 activity), vitamin E and selenium), and adiposity in patients with T2DM at high risk of cardio-renal disease. Women compared to men had higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
3
0
3
Order By: Relevance
“…CG8005, a potential deoxythreonate synthase, catalyzed the NAD-dependent oxidative cleavage of spermidine and interacted with eEF5 protein, which is involved in cell cycle progression, mRNA decay, the stress response, and maintenance of the cell wall integrity (http://flybase .org). The potential role of many antioxidants, such as NAC, to improve ROS-related stem cell self-renewal and differentiation disorders has been studied [37,38]. H 2 O 2 can exhibit its effect on cells through oxidative stress, which causes cells to gradually lose their ability to proliferate and eventually leads to cell death [39,40].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…CG8005, a potential deoxythreonate synthase, catalyzed the NAD-dependent oxidative cleavage of spermidine and interacted with eEF5 protein, which is involved in cell cycle progression, mRNA decay, the stress response, and maintenance of the cell wall integrity (http://flybase .org). The potential role of many antioxidants, such as NAC, to improve ROS-related stem cell self-renewal and differentiation disorders has been studied [37,38]. H 2 O 2 can exhibit its effect on cells through oxidative stress, which causes cells to gradually lose their ability to proliferate and eventually leads to cell death [39,40].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Известно, что дефицит данного фермента может усиливать атерогенез. Установлена связь между активностью ГП и развитием ССÇ, в том числе инфаркта миокарда [12] [13].…”
Section: глутатионпероксидазаunclassified
“…При изучении сердечно-почечных заболеваний авторы основное внимание уделили одной из семи изоформ ГП, а именно ГП3, экспрессирующейся преимущественно в эпителии почечных канальцев (в меньших количествах -в легких, печени, сердце, глазах, жировой ткани) и содержащей в активном центре селеноцистеин. Активность ГП3 снижается в связи с развитием окислительного стресса при почечной недостаточности [13]. Авторы приводят в пример работу А. Crawford et al, в которой сообщается о прямой связи между снижением активности ГП3 и ухудшением функции почек в течение одного года у пациентов с хронической болезнью почек (ХБП) [14].…”
Section: глутатионпероксидазаunclassified
“…Women reportedly have higher antioxidants activities compared to men. This is supported by the fact that women have higher glutathione levels as compared to men, due to oestrogens hormones that help to regulate antioxidant activities (Steyn, Zitouni, Kelly, Cook, & Earle, 2019). This suggested that GSH having potency to be one of the parameters in diagnosing blood glucose level.…”
Section: Introductionmentioning
confidence: 97%